Case Report: Neonatal Urinary Ascites Without Hydronephrosis: A Rare Case of Anterior Urethral Valve and Diverticulum in Preterm Newborn - He, Yue; Lin, Sam Bill; Li, WenXuan; Sun, YuBo; Tang, LiangFeng; Zhang, Rong (Frontiers in Pediatrics, 2022)
The deformation of congenital obstruction of the anterior urethra is rare in male infants. The anterior urethral valve (AUV) and diverticulum is not common cause of distal urethral obstruction, which may be significant but difficult to diagnose in time. We describe a premature infant who diagnosed with AUV as part of a diverticulum in the anterior urethra presented as massive urinary ascites without hydroureters and hydronephrosis. After Holmiun laser treatment, the infant’s urethral obstruction and massive ascites were successful resolved. We suggest that the presence of urinary ascites in fetuses and neonates should be considered as a warning against urinary malformations.